Social Empowerment of Isolated Customary Community - Teuku Murdani (Jurnal Penelitian Kesejahteraan Sosial, 2017)
Komunitas Adat Terpencil (KAT) is a program designed to improve both social life and economic condition for isolated customary communities. The aim of the program as stipulated in Indonesian national development planning isto afford the prosperity to every Indonesian citizen. This article is discussing a preparation phase of social community empowerment aiming to understand social condition and to absorb community aspirations on what they needs in affording social prosperity; Analyze the proper format of social empowerment to targeted community. The observation conducted in Dusun Pantan Kriko, Gampong Pantan Sinaku, Pintu Rime Gayo Sub-District, Bener Meriah District. The result of field study concluded that all local community members are coffee farmers, housing condition is really apprehensive, the houses are not appropriate to live, limited access to the social, health and education services. The primary needs are proper house, religious practice facility, community center building and its supporting facilities to facilitate meetings. Community sociological condition is really enthusiasm and ready to be empowered. Environment condition also very supported to develop various agriculture activities. Bener Meriah local government has declared the commitment to support and contribute to ensure the success of this social community empowerment program